Effect of boiling on texture of abalone muscles and its mechanism based on proteomic techniques. (15th September 2022) - Yu, Man-Man; Fan, Ying-Chen; Zhang, Xin-Ran; Li, De-Yang; Liu, Yu-Xin; Zhou, Da-Yong; Zhu, Bei-Wei
Highlights: Total 493 proteins were identified in water-soluble fraction using proteomics. The denaturation of hemocyanins and protein kinases were revealed by proteomics. 240 min-boiling caused the severe degradation of collagen and MPs. The oxidation and denaturation of proteins led to the increase of shear force. The degradation of MPs and collagen caused decreases in shear force and hardness. Abstract: The precise mechanism of texture changes in abalone muscles during boiling was investigated using quantitative proteomic analysis. A total 353 water-soluble proteins were identified in fresh abalone muscle. The number was decreased to 233 (6 min) and 201 (30 min), and then increased to 271 (240 min) during boiling. The undetectable protein in water-soluble fraction caused by boiling mainly belong to hemocyanins, protein kinases, dehydrogenases, phosphorylases, and transferases, while the newly identified proteins in water-soluble fraction during boiling mainly belong to collagen and myofibrillar proteins (MPs).Additionally, results also showed that boiling caused protein oxidation, denaturation, aggregation, crosslinking and degradation. Combined with the texture changes of abalone muscles during boiling, it was speculated that the oxidation, denaturation, aggregation and crosslinking of proteins led to the increase of shear force, however, the degradation of structural proteins such as MPs and collagen caused the decreases in shear force and hardness.